A bitter choice turned sweet: How acknowledging individuals' concern at having a low relative income serves to align utilitarianism and egalitarianism - Oded Stark; Marcin Jakubek; Martyna Kobus (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
When individuals' utility is a convex combination of their income and their concern at having a low relative income (the weights attached to income and to the concern at having a low relative income sum up to one), the maximization of aggregate utility yields an equal income distribution. This alignment of utilitarianism and egalitarianism is obtained for any number of individuals, and for general utility functions that are convex combinations of a power function of income and the concern at having a low relative income. The alignment can also hold when the weights sum up to a number different than one.
Keywords: H0; I0; I30; I31; 330; Utilitarianism; Egalitarianism; Social welfare maximization; Low relative income